1998
DOI: 10.1038/sj.onc.1201617
|View full text |Cite
|
Sign up to set email alerts
|

The CXXC Zn binding motifs of the human papillomavirus type 16 E7 oncoprotein are not required for its in vitro transforming activity in rodent cells

Abstract: The conserved region 3 (CR3) of the E7 protein of human papillomaviruses contains two CXXC motifs involved in zinc binding and in the homodimerization of the molecule. Studies have suggested that the intact CXXC motifs in the CR3 of HPV16 and HPV18 E7 are required for the in vitro transforming activity of these proteins. CR3 also contains a low anity pRb binding site and is involved in the disruption of the E2F/Rb1 complex. E7 is structurally and functionally related to Adenovirus E1A protein, which also has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The coordinated zinc ions are not directly involved in the E7 dimerization (Figure 3c) yet they are reported to be essential for that process (McIntyre et al, 1993;Braspenning et al, 1998;Clements et al, 2000;Alonso et al, 2002). Ethylenediaminetetraacetate led to the disappearance of disperse amide resonances in 1 H-15 N HSQC spectra of HPV45 E7 (data not shown) indicating that removal of zinc causes unfolding of the CR3 region.…”
Section: E7 Interaction With P21 Cip1mentioning
confidence: 98%
See 1 more Smart Citation
“…The coordinated zinc ions are not directly involved in the E7 dimerization (Figure 3c) yet they are reported to be essential for that process (McIntyre et al, 1993;Braspenning et al, 1998;Clements et al, 2000;Alonso et al, 2002). Ethylenediaminetetraacetate led to the disappearance of disperse amide resonances in 1 H-15 N HSQC spectra of HPV45 E7 (data not shown) indicating that removal of zinc causes unfolding of the CR3 region.…”
Section: E7 Interaction With P21 Cip1mentioning
confidence: 98%
“…The C-terminal region of E7 (CR3) contains two CXXC zinc-binding motifs separated by 29 residues (Barbosa et al, 1989). CR3 is responsible for the zinc-dependent dimerization (McIntyre et al, 1993;Braspenning et al, 1998;Clements et al, 2000;Alonso et al, 2002) and for (co-) mediating the interaction of E7 with a large number of diverse cellular proteins involved in the regulation of cell cycle progression and apoptosis, among them pRb and the cyclin-dependent kinase inhibitor (CDKI) p21 CIP1 (Zwerschke and Jansen-Durr, 2000;Munger et al, 2001). p21 CIP1 is the prototypical member of the CIP/KIP family of CDKIs, which share significant sequence homology in their N-terminal cyclin-CDK-binding domains.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the E7 proteins of HPV16 and HPV18 have indicated that the C terminus is required to maintain a stable and functional structure of the protein (9,13,34,51). CR3 contains two Cys-X-X-Cys motifs necessary for zinc binding and subsequent folding of the protomer into a unique viral ␤1␤2␣1␤3␣2 topology.…”
Section: Discussionmentioning
confidence: 99%
“…Such motifs have been previously described in members of the thioredoxin family, in DNA methyltransferase 1, CpG-binding protein, methyl-binding protein, and trithorax/ALL-1/ MLL (Ma et al, 1993;Bestor and Verdine, 1994;Hendrich and Bird, 1998;Voo et al, 2000). CXXC motifs, which like zinc and RING fingers, can also coordinate zinc atoms, are involved in the catalysis of redox reactions by thiol : disulfide oxidoreductases and in the maintenance of protein conformation and homodimerization (Chivers et al, 1996(Chivers et al, , 1997Braspenning et al, 1998;Collet et al, 2003;Fomenko and Gladyshev, 2003).…”
Section: Onzin Is Highly Conserved and Its Expression Is Tissue-restrmentioning
confidence: 99%